2011
DOI: 10.1016/j.psychres.2010.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Childhood physical abuse, aggression, and suicide attempts among criminal offenders

Abstract: Childhood physical abuse (CPA) has numerous short and long-term negative effects. One of the most serious consequences of CPA is an increased risk for suicide attempts. Clarifying the mechanisms by which CPA increases risk for suicidal behavior may enhance preventative interventions. One potential mechanism is a tendency toward aggression. In a sample of 266 criminal offenders, ages 18-62, we examined the relationships among CPA, lifetime aggression, and suicide attempts and tested lifetime history of aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 67 publications
10
41
0
Order By: Relevance
“…In prisoners significant relationships were earlier reported between childhood trauma scores and aggression scores (Sarchiapone, Carli, Cuomo et al, 2009b). Similarly Swogger, You, Cashman-Brown et al (2011), among 266 criminal offenders, showed that aggression scores on the Life History of Aggression Questionnaire (LHAQ) mediated the relationship between childhood physical abuse and attempting suicide.…”
Section: Discussionmentioning
confidence: 94%
“…In prisoners significant relationships were earlier reported between childhood trauma scores and aggression scores (Sarchiapone, Carli, Cuomo et al, 2009b). Similarly Swogger, You, Cashman-Brown et al (2011), among 266 criminal offenders, showed that aggression scores on the Life History of Aggression Questionnaire (LHAQ) mediated the relationship between childhood physical abuse and attempting suicide.…”
Section: Discussionmentioning
confidence: 94%
“…One such area of inquiry has focused on the influence of trauma and adversity on childhood aggression. Many studies have shown that children who are physically abused (Dodge et al 1990;Farrington 1978;Klika et al 2012;Swogger et al 2011;Widom 1989), emotionally abused (Allen 2011), neglected (Kotch et al 2008), witness domestic violence (Sousa et al 2010), or have an incarcerated family member (Murray et al 2012;Wildeman, 2010) are much more likely to display aggressive tendencies later in life.…”
Section: Aggressionmentioning
confidence: 99%
“…It has been associated specifically with personality disorder, psychotic symptoms, dissociative states, externalizing behavior (substance use and violence), and internalizing disorders (depression and anxiety) (Arboleda-Flores & Wade, 2001;Roe-Sepowitz, 2007;Roy, 2009;Swogger, You, CashmanBrown, & Conner, 2011). Criminal offenders have high rates of childhood trauma and suicide attempts (Clements-Nolle, Wolden, & BargmannLosche, 2009;Howard, Lennings, & Copeland, 2003;Swogger et al, 2011). Studies have identified the presence of negative emotions such as distress, hopelessness, and shame in female inmates with a history of childhood abuse, a form of childhood trauma, and postulate that these are important risk factors for suicidal and other self-harm behaviors in this population (Chapman, Specht, & Cellucci, 2005;Clements-Nolle et al, 2009;Milligan & Andrews, 2005).…”
Section: Childhood Traumamentioning
confidence: 99%
“…Studies have identified the presence of negative emotions such as distress, hopelessness, and shame in female inmates with a history of childhood abuse, a form of childhood trauma, and postulate that these are important risk factors for suicidal and other self-harm behaviors in this population (Chapman, Specht, & Cellucci, 2005;Clements-Nolle et al, 2009;Milligan & Andrews, 2005). Biological theories postulate that child abuse may result in attenuated serotonergic activity which may underlie impulsivity, in turn leading to a greater propensity to act on aggressive impulses toward the self or others (Swogger, et al, 2011).…”
Section: Childhood Traumamentioning
confidence: 99%